The Role of Scientific Research Activities for Lecturers of Universities, Colleges - Thi Hau, Trinh; Hoan, Le Ngoc (International Journal of Humanities and Education Development (IJHED), 2022)
Currently, any university has two main and most important tasks: training and scientific research. These are two activities that have an organic relationship, two basic strategic tasks of the school, in which the active participation of faculty members in scientific research activities is one of the important measures - mandatory - necessary to aim to improve the quality of training, to better meet the increasingly demanding needs of society. The content of this article focuses on analyzing several issues about the role of scientific research for university lecturers today